Indonesian's Position in the World Vegetable Oil Trade - Saleh Husin; Chandra Wijaya; Hanief Saha Ghafur; Eugenia Mardanugraha; T. M. Zakir Machmud (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2023)
Indonesia's position as the largest vegetable oil producer is very strong in the world trade. Nonetheless, the Netherlands and Malaysia trade the Indonesian palm oil, which leads to a significant generation of profits. This research demonstrates the role of Indonesia in the global trade of vegetable oil. It illustrates the rivalry among vegetable oil producers and exporters and the dependence of vegetable oil importers on Indonesia. The annual volume data of vegetable oil production, export, and import sourced from FAO STAT in 2010-2020 were used. The data were processed and analyzed using descriptive statistics. Palm oil is the most widely acquired vegetable oil. The production of this oil is plentiful, and its price is the most economical compared to other vegetable oils. Soybean oil was the main competitor of palm oil, with the primary producers being China and the United States. The negative campaign against Indonesian palm oil could not weaken Indonesia's competitiveness in the global vegetable oil trade. Indonesia should limit palm oil exports to Europe and Malaysia while increasing exports to countries that only use it for domestic consumption. Coconut oil had the most potential to increase vegetable oil production in Indonesia. Indonesia's prominence in the global trade of edible oil is supreme. However, this preeminent status may be deteriorated by nations engaged in the commerce of Indonesian palm oil. Therefore, Indonesia should continuously update the world vegetable oil trade map to emphasize the point and level of export elevation or reduction. Indonesia should also develop and increase the production of other vegetable oil products to strengthen its position in the world's oil trade.